Changes in the Positivity of Migrant Stereotype Content: How System-Sanctioned Pro-Migrant Ideology Can Affect Public Opinions of Migrants. Issue 2 (March 2018) - Gaucher, Danielle; Friesen, Justin P.; Neufeld, Katelin H. S.; Esses, Victoria M.
Complementing well-established antecedents of anti-migrant opinion (e.g., threat), we investigated how system-sanctioned ideologies—that is, the collection of beliefs and values espoused by the government in power—are linked with migrant stereotypes. Using Canada as a case study, across three waves of national survey data ( N = 1, 080), we found that system-sanctioned pro -migrant ideologies corresponded with (relatively) more positive migrant stereotype content (i.e., increases in perceived warmth and competence). Moreover, controlling for other political ideologies, increases in migrant stereotype positivity were linked to people's motivation to justify their sociopolitical systems, suggesting that system-sanctioned ideologies may be especially likely to influence the positivity of migrant stereotypes when people are motivated to justify their sociopolitical systems.